Composite negative electrode material, preparation method thereof, negative electrode plate applying composite negative electrode material and lithium battery
By forming a composite negative electrode material with a copolymer coated layer on the surface of the silicon negative electrode material, the problem of volume expansion and poor conductivity of the silicon negative electrode material during the charging and discharging process is solved, and the cycle life, rate performance and fast charging performance of the lithium battery are significantly improved.
Patent Information
- Application Number
- CN202411901428.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-20
AI Technical Summary
The silicon negative electrode material has large volume expansion and poor conductivity during charging and discharging, which limits its application in fast-charge lithium batteries.
A composite negative electrode material is used, which includes a silicon-based material and a cladding layer disposed on the surface of the silicon-based material, the cladding layer consists of a copolymer formed by copolymerization and comprises a specific first monomer and a second monomer to improve conductivity and stability.
Through the protection of the cladding layer, the loss of electrolyte components is reduced, the cycle life of lithium batteries and the first Coulomb efficiency is improved; the volume expansion of silicon-based materials is buffered, the risk of SEI film rupture is reduced, and the circulation performance is improved; the conductivity of silicon-based materials is improved, and the rate performance and fast charging performance are improved.
Smart Images

Figure BDA0005204010730000011 
Figure BDA0005204010730000021 
Figure BDA0005204010730000031
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a composite negative electrode material and a preparation method thereof, a negative electrode sheet and a lithium battery using the composite negative electrode material. Background Art
[0002] Graphite-based negative electrode materials are the most important negative electrode materials currently used in lithium batteries, including natural graphite, artificial graphite, mesophase carbon microspheres and other forms. Graphite-based negative electrode materials have high safety, good rate performance, small volume expansion after lithium insertion (<10%), good cycle performance, low price and no pollution. In the process of lithium ion embedding into the negative electrode, lithium ions and graphite form graphite intercalation compound LiC6, which provides a theoretical specific capacity of 372mAh / g. The low theoretical specific capacity of graphite-based negative electrode materials makes it difficult to meet the increasing capacity requirements of lithium batteries, thus limiting the development prospects of graphite-based negative electrode materials.
[0003] Among the many lithium battery negative electrode materials, silicon is the most popular because it can form Li x Si is considered to be the most promising alternative to graphite anodes because of its extremely high specific capacity. The theoretical specific capacity of silicon is as high as 4200mAh / g, and its relatively high reaction potential (~0.4V vs.Li + / Li) makes it an ideal material for preparing lithium batteries with high energy density. However, silicon has a large volume expansion (>300%) and poor electronic conductivity (1.56×10 -3 S / cm) will lead to increased polarization, shedding of active materials, rapid capacity decay and other problems, which limit its application in fast-charging lithium batteries. Summary of the invention
[0004] In order to solve the problems of large volume expansion and poor conductivity of silicon negative electrode materials during charge and discharge, the present invention provides a composite negative electrode material and a preparation method thereof, a negative electrode sheet and a lithium battery using the composite negative electrode material.
[0005] According to a first aspect of the present invention, there is provided a composite negative electrode material, the composite negative electrode material comprising a silicon-based material and a coating layer disposed on the surface of the silicon-based material, the coating layer comprising a copolymer, the copolymer comprising a first monomer as shown in Formula I and a second monomer as shown in Formula II;
[0006]
[0007]
[0008] X is a heterocyclic ring containing an O atom;
[0009] R1 is selected from one of —H, alkyl, and —NH2, R2 is selected from one of —H, alkyl, and —NH2, and at least one of R1 and R2 is —NH2.
[0010] In the composite negative electrode material provided by the present invention, a copolymer formed by copolymerization of a first monomer as shown in Formula I and a second monomer as shown in Formula II is used to coat a silicon-based material, and the composite negative electrode material is applied to a negative electrode sheet and a lithium battery. First, the coating layer can protect the silicon-based material from direct contact with the electrolyte, thereby reducing the loss of electrolyte components, protecting the stability of the electrode structure, and improving the cycle life and the first coulomb efficiency of the lithium battery. Second, during the charging and discharging process of the lithium battery, the coating layer can buffer the volume expansion of the silicon-based material, reduce the risk of rupture of the SEI film formed on the surface of the negative electrode sheet due to the volume expansion of the silicon-based material during the charging and discharging process, thereby improving the cycle performance of the lithium battery. Third, the copolymer used to form the coating layer has strong adhesion properties, and because it contains the first monomer, the coating layer formed by it has high The characteristic of conductivity can improve the problem of low conductivity of silicon-based materials, thereby improving the rate performance of lithium batteries. At the same time, its conductivity will not decrease significantly due to the increase in temperature. This characteristic enables the lithium battery to maintain excellent rate performance when the temperature of the lithium battery increases due to the internal chemical reaction heat generation during the cyclic charge and discharge process, especially the lithium battery is easy to heat up during the fast charging process. Due to the presence of the coating layer, the lithium battery using silicon-based materials has good fast charging performance. Fourth, the -NH2 contained in the second monomer contained in the copolymer used to form the coating layer can form a hydrogen bond with the hydroxyl group on the surface of the silicon-based material, improve the stability of the coating layer, and then improve the cycle performance of the lithium battery using the composite negative electrode material, so that the lithium battery can still maintain good cycle stability and high capacity retention rate after multiple charge and discharge cycles. Therefore, the composite negative electrode material provided by the present invention improves the first coulomb efficiency, cycle performance, rate performance and fast charging performance of the lithium battery using it through the effects of the above four aspects, thereby extending the cycle life of the lithium battery.
[0011] Preferably, the above copolymer comprises a first monomer as shown in formula III and a second monomer as shown in formula IV;
[0012]
[0013] The composite negative electrode material involved in this scheme uses a copolymer formed by copolymerization of a first monomer as shown in Formula III and a second monomer as shown in Formula IV to coat a silicon-based material, so that the initial coulombic efficiency, cycle performance, and rate performance of a lithium battery using the composite negative electrode material are further improved.
[0014] Preferably, the molar ratio of the first monomer to the second monomer is 1:1-10.
[0015] By controlling the molar ratio of the first monomer and the second monomer in the copolymer used to form the coating layer within the above range, the conductivity of the coating layer is ensured, which is beneficial to better improve the conductivity of the silicon-based material, and the hydrogen bonding force between the coating layer and the silicon-based material can be ensured.
[0016] If the molar ratio of the first monomer to the second monomer is too small, that is, the second monomer is too much, the coating layer will have too little effect on improving the conductivity of the silicon-based material; if the molar ratio of the first monomer to the second monomer is too large, that is, the first monomer is too much, the hydrogen bonding force between the coating layer and the silicon-based material will be too small.
[0017] Preferably, the molar ratio of the first monomer to the second monomer is 1:5.
[0018] Preferably, the number average molecular weight of the copolymer is 5,000 to 30,000.
[0019] The number average molecular weight of the copolymer used to form the coating layer is controlled within the above range. Firstly, the bonding strength of the coating layer can be maintained within an appropriate range, which is beneficial to reducing the risk of the coating layer falling off or peeling off during multiple cycles of charge and discharge of the composite negative electrode material. Secondly, the coating layer has good mechanical strength, which can improve the buffering effect of the coating layer on the volume expansion of silicon during the charge and discharge of the composite negative electrode material. Thirdly, the coating layer has good uniformity and density, which can improve the cycle stability of the composite negative electrode material during the charge and discharge process.
[0020] If the number average molecular weight of the copolymer used to form the coating layer is too small, the bonding strength of the coating layer will be low, the coating layer will easily fall off or peel off during the charge and discharge cycle, and the mechanical strength of the copolymer will be low; if the number average molecular weight of the copolymer used to form the coating layer is too large, the solubility of the copolymer in organic solvents will be poor, which will increase the difficulty of coating and also affect the uniformity and density of the coating layer.
[0021] Preferably, the particle size D50 of the composite negative electrode material is 4 to 9 μm.
[0022] Controlling the particle size D50 of the composite negative electrode material within the above range can not only keep the lithium ion transmission path within an appropriate range, but also ensure the compaction density of the negative electrode sheet made using the composite negative electrode material and the energy density of the lithium battery.
[0023] Preferably, the specific surface area of the composite negative electrode material is 2 to 8 m 2 / g.
[0024] Preferably, the silicon content in the silicon-based material is 20-80 wt%.
[0025] Controlling the silicon content in the silicon-based material in the composite negative electrode material within the above range and applying it to the negative electrode sheet and lithium battery can not only ensure the energy density and rate performance of the lithium battery, but also avoid the risk of excessive silicon content causing excessive volume expansion of the silicon-based material during charging and discharging, which may lead to rupture of the composite negative electrode material.
[0026] If the silicon content in the silicon-based material of the composite negative electrode material is too high, the silicon-based material will expand too much during the charge and discharge process, making it more prone to the risk of rupture; if the silicon content in the silicon-based material of the composite negative electrode material is too low, the energy density and rate performance of the lithium battery using it will decrease.
[0027] Preferably, the coating layer accounts for 1 to 8% by mass in the composite negative electrode material.
[0028] Preferably, the coating layer has a thickness of 10 to 150 nm.
[0029] Controlling the mass percentage and thickness of the coating layer within the above range can further improve the lithium ion transmission performance, rate performance and cycle performance of the composite negative electrode material, and the coating layer has good flexibility.
[0030] If the mass proportion of the coating layer is too small and the thickness is too thin, the coating layer will easily break during multiple cycles of charge and discharge, resulting in loss of active lithium; if the mass proportion of the coating layer is too large and the thickness is too thick, the ion transport performance of the composite negative electrode material will be poor, resulting in a decrease in its rate performance and cycle performance.
[0031] Preferably, the silicon-based material includes at least one of silicon monoxide (SiO) and silicon carbon material (SiC).
[0032] Preferably, the silicon-carbon material includes a porous carbon skeleton, a silicon layer and a carbon layer, the porous carbon skeleton includes an inner layer region and an outer layer region wrapping the inner layer region, the inner layer region has a plurality of inner holes, the outer layer region has a plurality of outer holes, the silicon layer is arranged on the inner walls of the inner holes and the outer holes, and the carbon layer is arranged on the surface of the silicon layer in the outer holes, so that the silicon-carbon particles have inner pores in the inner layer region and outer pores in the outer layer region.
[0033] Preferably, among the internal pores and external pores of the silicon-carbon material, the proportion of mesopores is 42-86%, and the proportion of micropores is less than 58%, wherein the diameter of the mesopores is 3-40 nm, and the diameter of the micropores is 0.5-2 nm.
[0034] According to a second aspect of the present invention, there is provided a method for preparing a composite negative electrode material, comprising the following steps:
[0035] S1. constructing a three-electrode system, wherein the three-electrode system comprises a working electrode, a counter electrode and a reference electrode, the working electrode comprises one of a platinum electrode and a glassy carbon electrode, the counter electrode comprises a platinum electrode, and the reference electrode comprises a silver / silver chloride electrode;
[0036] S2. An electrolyte solution is prepared using an electrolyte and an organic solvent, wherein the electrolyte comprises at least one of LiClO4 and tetrabutylammonium perchlorate;
[0037] S3. dissolving the first monomer as shown in formula Ⅰ and the second monomer as shown in formula Ⅱ in the electrolyte solution to obtain a first mixed solution;
[0038] S4. The working electrode of the three-electrode system is immersed in the first mixed solution and reacted at a constant voltage of 0.8 to 1.8 V for 600 to 1500 s to obtain a copolymer;
[0039] S5. A copolymer solution is prepared by using a copolymer and an organic solvent;
[0040] S6. applying the copolymer solution to the surface of the silicon-based material, and drying the copolymer solution on the surface of the silicon-based material to form a coating layer on the surface of the silicon-based material to obtain a composite negative electrode material;
[0041]
[0042] X is a heterocyclic ring containing an O atom;
[0043] R1 is selected from one of —H, alkyl, and —NH2, R2 is selected from one of —H, alkyl, and —NH2, and at least one of R1 and R2 is —NH2.
[0044] Compared with other copolymerization methods, this scheme dissolves the first monomer and the second monomer in an electrolyte solution and uses a three-electrode system to pressurize the first monomer and the second monomer to form a copolymer to coat the silicon-based material. The prepared composite negative electrode material is applied to lithium batteries, which can improve the initial coulombic efficiency, cycle performance, rate performance and fast charging performance of lithium batteries, thereby extending the cycle life of lithium batteries.
[0045] Preferably, in S3, the first monomer is as shown in formula III, and the second monomer is as shown in formula IV;
[0046]
[0047] Preferably, in S1, the concentration of the prepared electrolyte solution is 0.05-0.2 mol / L.
[0048] Preferably, in S3, the molar ratio of the first monomer to the second monomer is 1:1-10.
[0049] Preferably, in S3, the molar ratio of the first monomer to the second monomer is 1:1-5.
[0050] Preferably, in S4, the number average molecular weight of the copolymer prepared is 5,000 to 30,000.
[0051] Preferably, in S5, the organic solvent includes at least one of benzene, toluene, tetrahydrofuran (THF), and N,N-dimethylformamide (DMF).
[0052] Preferably, in S5, the mass fraction of the copolymer solution is 5 to 18%.
[0053] Preferably, in S6, the particle size D50 of the silicon-based material is 4-9 μm.
[0054] Preferably, in S6, the specific surface area of the silicon-based material is 2 to 8 m 2 / g.
[0055] Preferably, in S6, the silicon content in the silicon-based material is 20-80 wt%.
[0056] Preferably, in S6, the mass proportion of the formed coating layer in the composite negative electrode material is 1-8%.
[0057] Preferably, in S6, the thickness of the formed coating layer is 10 to 150 nm.
[0058] Preferably, in S6, the silicon-based material includes at least one of silicon monoxide (SiO) and silicon carbon material (SiC).
[0059] Preferably, among the internal pores and external pores of the silicon-carbon material, the proportion of mesopores is 42-86%, and the proportion of micropores is less than 58%, wherein the diameter of the mesopores is 3-40 nm, and the diameter of the micropores is 0.5-2 nm.
[0060] Preferably, S6 includes the following operations: mixing the silicon-based material and the copolymer solution and stirring at 40-80° C. for 4-10 hours to obtain a second mixed solution, and spray-drying the mixed solution to obtain a composite negative electrode material.
[0061] Preferably, in S6, the inlet temperature of the spray drying is 100-200°C, and the outlet temperature is 50-90°C.
[0062] According to a third aspect of the present invention, a negative electrode sheet is provided, which includes a negative electrode collector and a negative electrode active material layer arranged on the surface of the negative electrode collector, and the negative electrode active material layer contains the above-mentioned composite negative electrode material or a composite negative electrode material prepared by the above-mentioned composite negative electrode material preparation method.
[0063] According to a fourth aspect of the present invention, a lithium battery is provided, comprising the negative electrode sheet described above.
[0064] The composite negative electrode material provided by the present invention is applied to negative electrode sheets and lithium batteries, giving the batteries excellent first coulombic efficiency, cycle performance, rate performance and fast charging performance, thereby extending the cycle life of the lithium battery. DETAILED DESCRIPTION
[0065] The following is a further clear and complete description of the technical features in the technical solution provided by the present invention in conjunction with the specific implementation methods. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0066] Example 1
[0067] A lithium battery is prepared by the following steps:
[0068] 1. Preparation of negative electrode
[0069] The composite negative electrode material, conductive carbon black (SP), single-walled carbon nanotube (SWCNT), and binder polyacrylic acid (PAA) were mixed in a mass ratio of 80:9:1:10 and added into deionized water as a solvent, and mixed evenly to prepare a negative electrode slurry with a solid content of 30%. The negative electrode slurry was coated on both surfaces of the negative electrode current collector copper foil to form a negative electrode active material layer, and after vacuum drying and cold pressing, a negative electrode sheet was prepared;
[0070] The composite negative electrode material comprises a silicon-based material and a coating layer disposed on the surface of the silicon-based material, wherein the coating layer contains a copolymer, and the copolymer comprises a first monomer as shown in Formula III and a second monomer as shown in Formula IV;
[0071]
[0072] The above composite negative electrode material is prepared by the following steps:
[0073] S1. Construct a three-electrode system containing a working electrode, a counter electrode and a reference electrode;
[0074] Among them, the working electrode is a glassy carbon electrode, the counter electrode is a platinum electrode, and the reference electrode is a silver / silver chloride electrode;
[0075] S2. An electrolyte solution having a concentration of 0.1 mol / L was prepared using electrolyte LiClO4 and an organic solvent THF;
[0076] S3. dissolving the first monomer and the second monomer in the electrolyte solution to obtain a first mixed solution;
[0077] Wherein, the molar ratio of the first monomer to the second monomer is 1:5;
[0078] S4. The mixed solution was injected into the three-electrode system to ensure that the working electrode was completely immersed in the first mixed solution, and a constant voltage of 1.3 V was used for pressure reaction for 1000 s. After the reaction was completed, the working electrode was taken out and washed with dichloromethane to remove unreacted monomers and electrolyte residues to obtain a copolymer with a number average molecular weight between 18000 and 20000;
[0079] S5. A copolymer solution having a mass fraction of 11% was prepared by using the copolymer and an organic solvent THF;
[0080] S6. Add the silicon-based material to the copolymer solution and stir at 60°C for 7h to obtain a second mixed solution, spray-dry the second mixed solution to form a coating layer with a thickness of 80nm on the surface of the silicon-based material, and obtain a composite negative electrode material with a particle size D50 of 6μm, wherein the coating layer accounts for 5% by mass in the composite negative electrode material, the inlet temperature of the spray drying is 150°C, and the outlet temperature is 70°C;
[0081] The silicon-based material involved in this embodiment is silicon-carbon material.
[0082] 2. Preparation of positive electrode
[0083] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2, conductive carbon black (SP) and binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 96:2:2 and added to a solvent N-methylpyrrolidone (NMP). The mixture is evenly mixed to obtain a positive electrode slurry with a solid content of 45%. The positive electrode slurry is coated on both surfaces of the positive electrode current collector aluminum foil to form a positive electrode active coating. After vacuum drying and cold pressing, a positive electrode sheet is obtained.
[0084] 3. Preparation of Diaphragm
[0085] A polyethylene (PE) film containing a ceramic layer is used as the diaphragm.
[0086] 4. Preparation of Electrolyte
[0087] Ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and fluoroethylene carbonate (FEC) are mixed in a mass ratio of 20:40:30:10 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the organic solvent to prepare an electrolyte with a concentration of 1M.
[0088] 5. Assembly of lithium batteries
[0089] The positive electrode sheet, separator and negative electrode sheet are stacked in order, so that the separator is placed between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell, which is placed in an outer packaging shell, dried and injected with the above-mentioned electrolyte, and subjected to vacuum packaging, standing, forming, shaping and other processes to obtain a lithium battery.
[0090] Example 2
[0091] This embodiment provides a lithium battery. Compared with the embodiment 1, the difference in structure is that the preparation method of the composite negative electrode material used in the negative electrode sheet is different.
[0092] The composite negative electrode material used in this embodiment is prepared by the following steps:
[0093] S1. Construct a three-electrode system containing a working electrode, a counter electrode and a reference electrode;
[0094] Among them, the working electrode is a glassy carbon electrode, the counter electrode is a platinum electrode, and the reference electrode is a silver / silver chloride electrode;
[0095] S2. An electrolyte solution having a concentration of 0.05 mol / L was prepared using electrolyte LiClO4 and an organic solvent THF;
[0096] S3. dissolving the first monomer and the second monomer in the electrolyte solution to obtain a first mixed solution;
[0097] Wherein, the molar ratio of the first monomer to the second monomer is 1:1;
[0098] S4. The mixed solution is injected into the three-electrode system, ensuring that the working electrode is completely immersed in the first mixed solution, and a constant voltage of 0.8 V is used for pressure reaction for 1500 seconds. After the reaction is completed, the working electrode is taken out and washed with dichloromethane to remove unreacted monomers and electrolyte residues to obtain a copolymer with a number average molecular weight between 3000 and 4000;
[0099] S5. A copolymer solution having a mass fraction of 5% was prepared by using the copolymer and an organic solvent THF;
[0100] S6. Add the silicon-based material to the copolymer solution and stir at 40°C for 10 hours to obtain a second mixed solution. Spray-dry the second mixed solution to form a coating layer with a thickness of 10 nm on the surface of the silicon-based material to obtain a composite negative electrode material with a particle size D50 of 4 μm, wherein the mass proportion of the coating layer in the composite negative electrode material is 1%, the inlet temperature of the spray drying is 100°C, and the outlet temperature is 50°C.
[0101] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.
[0102] Example 3
[0103] This embodiment provides a lithium battery. Compared with the embodiment 1, the difference in structure is that the preparation method of the composite negative electrode material used in the negative electrode sheet is different.
[0104] The composite negative electrode material used in this embodiment is prepared by the following steps:
[0105] S1. Construct a three-electrode system containing a working electrode, a counter electrode and a reference electrode;
[0106] Among them, the working electrode is a glassy carbon electrode, the counter electrode is a platinum electrode, and the reference electrode is a silver / silver chloride electrode;
[0107] S2. An electrolyte solution having a concentration of 0.2 mol / L was prepared using electrolyte LiClO4 and an organic solvent THF;
[0108] S3. dissolving the first monomer and the second monomer in the electrolyte solution to obtain a first mixed solution;
[0109] Wherein, the molar ratio of the first monomer to the second monomer is 1:10;
[0110] S4. The mixed solution was injected into the three-electrode system to ensure that the working electrode was completely immersed in the first mixed solution, and a constant voltage of 1.8 V was used for a pressure reaction for 600 seconds. After the reaction was completed, the working electrode was taken out and washed with dichloromethane to remove unreacted monomers and electrolyte residues to obtain a copolymer with a number average molecular weight between 28,000 and 30,000;
[0111] S5. A copolymer solution having a mass fraction of 18% was prepared by using the copolymer and an organic solvent THF;
[0112] S6. Add the silicon-based material to the copolymer solution and stir at 80°C for 4 hours to obtain a second mixed solution. Spray-dry the second mixed solution to form a coating layer with a thickness of 150 nm on the surface of the silicon-based material to obtain a composite negative electrode material with a particle size D50 of 9 μm, wherein the mass proportion of the coating layer in the composite negative electrode material is 8%, the inlet temperature of the spray drying is 200°C, and the outlet temperature is 90°C.
[0113] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.
[0114] Example 4
[0115] This embodiment provides a lithium battery. Compared with the embodiment 1, the difference in structure is that the coating layer in the composite negative electrode material contains a different copolymer, and the first monomer used is as shown in formula V;
[0116]
[0117] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.
[0118] Example 5
[0119] This embodiment provides a lithium battery, which is different from that of embodiment 1 in that the coating layer in the composite negative electrode material contains a different copolymer, and the second monomer used is as shown in formula VI;
[0120]
[0121] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.
[0122] Example 6
[0123] This embodiment provides a lithium battery. Compared with the embodiment 1, the difference in structure is that the coating layer in the composite negative electrode material contains a different copolymer, and the second monomer used is as shown in formula VII;
[0124]
[0125] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.
[0126] Example 7
[0127] This embodiment provides a lithium battery. Compared with Embodiment 1, the difference in structure is: in the preparation step S4 of the composite negative electrode material, the mixed solution is injected into the three-electrode system to ensure that the working electrode is completely immersed in the first mixed solution, and a constant voltage of 1.3V is used for pressure reaction for 500s, and the number average molecular weight of the obtained copolymer is 3000-4000.
[0128] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.
[0129] Example 8
[0130] This embodiment provides a lithium battery. Compared with Embodiment 1, the difference in structure is: in the preparation step S3 of the composite negative electrode material, the mixed solution is injected into the three-electrode system to ensure that the working electrode is completely immersed in the first mixed solution, and a constant voltage of 1.3V is used for pressure reaction for 2500s, and the number average molecular weight of the obtained copolymer is 33000-35000.
[0131] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.
[0132] Example 9
[0133] This embodiment provides a lithium battery. Compared with the embodiment 1, the difference in structure is that in the preparation step S3 of the composite negative electrode material, the molar ratio of the first monomer to the second monomer is 1:7.
[0134] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.
[0135] Example 10
[0136] This embodiment provides a lithium battery, and compared with Embodiment 1, the differences in structure are: (1) in the preparation step S5 of the composite negative electrode material, the mass fraction of the copolymer solution is 3%; (2) in the preparation step S6 of the composite negative electrode material, the particle size D50 of the composite negative electrode material finally obtained is 3 μm, the thickness of the formed coating layer is 7 nm, and the mass fraction of the coating layer in the composite negative electrode material is 0.5%.
[0137] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.
[0138] Embodiment 11
[0139] This embodiment provides a lithium battery, and compared with Embodiment 1, the differences in structure are: (1) in the preparation step S5 of the composite negative electrode material, the mass fraction of the copolymer solution is 20%; (2) in the preparation step S6 of the composite negative electrode material, the particle size D50 of the composite negative electrode material finally obtained is 10 μm, the thickness of the formed coating layer is 180 nm, and the mass fraction of the coating layer in the composite negative electrode material is 10%.
[0140] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.
[0141] Comparative Example 1
[0142] This comparative example provides a lithium battery. Compared with Example 1, the difference in structure is that the composite negative electrode material used in the preparation process of the negative electrode sheet is a silicon-based material without a coating layer.
[0143] Except for the above differences, the materials, formula ratios and preparation operations used in this comparative example are strictly consistent with those in Example 1.
[0144] Comparative Example 2
[0145] This comparative example provides a lithium battery, which is different from Example 1 in structure in that the coating layer in the composite negative electrode material contains a different copolymer, and the first monomer used is as shown in Formula VIII;
[0146]
[0147] Except for the above differences, the materials, formula ratios and preparation operations used in this comparative example are strictly consistent with those in Example 1.
[0148] Comparative Example 3
[0149] This comparative example provides a lithium battery, which is different from Example 1 in structure in that the coating layer in the composite negative electrode material contains a different copolymer, and the first monomer used is as shown in Formula IX;
[0150]
[0151] Except for the above differences, the materials, formula ratios and preparation operations used in this comparative example are strictly consistent with those in Example 1.
[0152] Comparative Example 4
[0153] This comparative example provides a lithium battery, which is different from Example 1 in structure in that the coating layer in the composite negative electrode material contains a different copolymer, and the first monomer used is as shown in Formula X;
[0154]
[0155] Except for the above differences, the materials, formula ratios and preparation operations used in this comparative example are strictly consistent with those in Example 1.
[0156] Comparative Example 5
[0157] This comparative example provides a lithium battery, which is different from Example 1 in structure in that the coating layer in the composite negative electrode material contains a different copolymer, and the second monomer used is as shown in Formula XI;
[0158]
[0159] Except for the above differences, the materials, formula ratios and preparation operations used in this comparative example are strictly consistent with those in Example 1.
[0160] Test Case
[0161] 1. Participants
[0162] In this test example, the lithium batteries prepared in Examples 1 to 11 and Comparative Examples 1 to 5 were used as test objects to conduct relevant performance tests.
[0163] 2. Test content
[0164] (1) First Coulomb efficiency
[0165] At 25°C, the lithium battery was charged to 4.2V at a constant current and constant voltage rate of 0.33C and allowed to stand for 10 minutes. Then, the lithium battery was discharged to 2.5V at a constant current rate of 0.33C and allowed to stand for 10 minutes. The first coulombic efficiency of the lithium battery was calculated.
[0166] First coulombic efficiency (%) = total capacity of lithium battery discharged at 0.33C for the first time / total capacity of lithium battery charged at 0.33C for the first time × 100%.
[0167] (2) Capacity retention rate after 1200 cycles at 1C / 1C at room temperature
[0168] At 25°C, the lithium battery is charged to 4.2V at a constant current and constant voltage rate of 1C, with a cut-off current of 0.05C, and allowed to stand for 10 minutes. Then, the lithium battery is discharged to 2.5V at a constant current rate of 1C and allowed to stand for 10 minutes. This is considered one charge and discharge cycle. The lithium battery is charged and discharged for 1200 cycles according to the above method, and the capacity retention rate after 1200 cycles of charge and discharge at 1C / 1C is calculated.
[0169] The capacity retention rate (%) of a lithium battery after N cycles = (discharge capacity at the Nth cycle / first discharge capacity) × 100%, where N is the number of cycles of the lithium battery.
[0170] (3) Room temperature 6C rate performance - constant current charging ratio
[0171] At 25°C, the lithium battery was discharged at a constant current rate of 1C to 2.5V and allowed to stand for 10 minutes. Then, the lithium battery was charged at a constant current and constant voltage rate of 6C to 4.2V, with a cut-off current of 0.05C and allowed to stand for 10 minutes. The 6C constant current charging capacity Q1, the 6C constant current and constant voltage charging total capacity Q2 and the highest temperature during the fast charging process (i.e., the highest temperature of 6C rate charging) of the lithium battery were recorded. The 6C rate charging constant current charging ratio was calculated according to the following formula: 6C rate charging constant current charging ratio = 6C constant current charging capacity Q1 / 6C constant current and constant voltage charging total capacity Q2 × 100%, wherein, the constant current and constant voltage charging total capacity Q2 = constant current charging capacity + constant voltage charging capacity.
[0172] (4) 1C / 10C discharge capacity retention rate at room temperature
[0173] At 25°C, the divided lithium battery is charged to 4.2V at a constant current and constant voltage rate of 1C, with a cut-off current of 0.05C. After standing for 10 minutes, the lithium battery is discharged to 2.5V at a constant current rate of 1C, and its discharge capacity Q is recorded. 1C As the initial discharge capacity; then at 25 ° C, the lithium battery is charged to 4.2V at a constant current and constant voltage rate of 1C, the cut-off current is 0.05C, and it is left to stand for 10 minutes. Then, the fully charged lithium battery is discharged to 2.5V at a constant current rate of 10C, and its discharge capacity Q is recorded. 10C ; Calculate the discharge capacity retention rate of the lithium battery at 1C / 10C rate according to the following formula: Discharge capacity retention rate (%) = discharge capacity Q at 10C rate 10C / Discharge capacity at 1C rate Q 1C ×100%.
[0174] 3. Experimental results
[0175] Table 1. Test results of relevant performance of lithium battery
[0176]
[0177] The relevant performance test results of the lithium batteries prepared in Examples 1 to 11 and Comparative Examples 1 to 5 are shown in Table 1.
[0178] The composite negative electrode material used in the lithium battery provided in Comparative Example 1 is a silicon-based material without a coating layer, while the composite negative electrode material used in the lithium battery provided in Examples 1 to 11 is prepared by coating a silicon-based material with a copolymer formed by a copolymerization reaction of a first monomer shown in Formula I and a second monomer shown in Formula II. The test results show that the first coulombic efficiency, the capacity retention rate of 1C / 1C cycle 1200 cycles at room temperature, the constant current charging ratio of 6C rate charging, and the discharge capacity retention rate of 1C / 10C at room temperature of the lithium-ion batteries provided in Examples 1 to 11 are significantly higher than those in Comparative Example 1. The above results indicate that coating a silicon-based material with a copolymer formed by a copolymerization reaction of a first monomer shown in Formula I and a second monomer shown in Formula II, and applying the composite negative electrode material to a negative electrode sheet and a lithium battery can improve the first coulombic efficiency, cycle performance, rate performance and fast charging performance of the lithium battery, thereby extending the cycle life of the lithium battery.
[0179] By comparing the test results of Examples 1, 4, 5, 6 and Comparative Examples 2, 3, 4, 5, it can be shown that compared with the first monomer and the second monomer of other structures, the composite negative electrode material prepared by coating the silicon-based material with a copolymer formed by the copolymerization reaction of the first monomer shown in Formula III and the second monomer shown in Formula IV in Example 1 has better first coulombic efficiency, cycle performance, rate performance and fast charging performance.
[0180] By comparing the test results of Examples 1, 7 and 8, it can be shown that the negative electrode active material obtained by coating the silicon-based material with a copolymer having a number average molecular weight in the range of 5000 to 30000 has better cycle performance and rate performance.
[0181] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.
Claims
1. A composite negative electrode material, characterized in that: The composite negative electrode material comprises a silicon-based material and a coating layer disposed on the surface of the silicon-based material, wherein the coating layer contains a copolymer, and the copolymer comprises a first monomer as shown in Formula I and a second monomer as shown in Formula II; The X is a heterocycle containing an O atom; The R1 is selected from one of —H, alkyl, and —NH2, the R2 is selected from one of —H, alkyl, and —NH2, and at least one of the R1 and the R2 is —NH2.
2. The composite negative electrode material according to claim 1, characterized in that: The copolymer includes a first monomer as shown in Formula III and a second monomer as shown in Formula IV; 3. The composite negative electrode material according to claim 1, characterized in that: The molar ratio of the first monomer to the second monomer is 1:1-10.
4. The composite negative electrode material according to claim 1, characterized in that: The number average molecular weight of the copolymer is 5,000 to 30,000.
5. The composite negative electrode material according to claim 1, characterized in that: The particle size D50 of the composite negative electrode material is 4 to 9 μm, and / or the specific surface area of the composite negative electrode material is 2 to 8 m 2 / g, and / or, the silicon content in the silicon-based material is 20-80wt%.
6. The composite negative electrode material according to claim 1, characterized in that: The coating layer accounts for 1 to 8% by mass of the composite negative electrode material, and / or the coating layer has a thickness of 10 to 150 nm.
7. A method for preparing a composite negative electrode material, characterized in that: The following steps are involved: S1. constructing a three-electrode system, wherein the three-electrode system comprises a working electrode, a counter electrode and a reference electrode, the working electrode comprises one of a platinum electrode and a glassy carbon electrode, the counter electrode comprises a platinum electrode, and the reference electrode comprises a silver / silver chloride electrode; S2. An electrolyte solution is prepared using an electrolyte and an organic solvent, wherein the electrolyte comprises at least one of LiClO4 and tetrabutylammonium perchlorate; S3. dissolving the first monomer as shown in formula Ⅰ and the second monomer as shown in formula Ⅱ in the electrolyte solution to obtain a first mixed solution; S4. The working electrode in the three-electrode system is immersed in the first mixed solution and subjected to a constant voltage reaction of 0.8 to 1.8 V for 600 to 1500 s to obtain a copolymer; S5. preparing a copolymer solution by using the copolymer and an organic solvent; S6. applying the copolymer solution to the surface of the silicon-based material, drying the copolymer solution on the surface of the silicon-based material to form the coating layer on the surface of the silicon-based material, and obtaining the composite negative electrode material; The X is a heterocycle containing an O atom; The R1 is selected from one of —H, alkyl, and —NH2, the R2 is selected from one of —H, alkyl, and —NH2, and at least one of the R1 and the R2 is —NH2.
8. The method for preparing the composite negative electrode material according to claim 7, characterized in that: In said S3, the first monomer is as shown in formula III, and the second monomer is as shown in formula IV; 9. A negative electrode sheet, characterized in that: The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer arranged on the surface of the negative electrode current collector, and the negative electrode active material layer contains the composite negative electrode material according to any one of claims 1 to 7 or a composite negative electrode material prepared by the preparation method of the composite negative electrode material according to claim 8.
10. A lithium battery, characterized in that: The lithium battery comprises the negative electrode sheet as claimed in claim 9.
Citation Information
Patent Citations
Silicon / PEDOT composite material, preparation method thereof and application thereof in serving as lithium ion battery cathode material
CN107204433A
Negative electrode material and preparation method and application thereof
CN114335473A
Silicon-based composite negative electrode material and preparation method thereof
CN115986076A
Negative active material as well as preparation method and application thereof
CN118572063A
Multilayer coated silicon carbon material and preparation method and application thereof
CN118867190A